Her2 status in gastric adenocarcinoma: comparison between matched endoscopic biopsy and gastrectomy specimens - Pham, Cuong H.; Tran, Yen N. H.; Thai, Tu A.; Lu, Kim B.; Cao, Nga N. T. (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Purpose: To evaluate the concordance between HER2 status in matched endoscopic biopsy and gastrectomy specimens of gastric adenocarcinoma patients. Patients and Methods: Fifty-five gastric adenocarcinoma patients were diagnosed by upper GI endoscopic biopsy and treated with gastrectomy. HER2 status was assessed by immunohistochemistry (IHC) and fluorescence in situ hybridisation (FISH) on both endoscopic biopsy and gastrectomy specimens. HER2-positive status was defined as a score IHC 3+, or IHC 2+ with a positive result in FISH. Data were collected from June, 2014 to July, 2016 in HCMC Oncology Hospital. Results: HER2-positive status was identified in 9.6%. The concordance in HER2 status between matched endoscopic biopsy and surgical specimens was 98% (Kappa=0.879). Conclusion: There was a very high concordance in HER2 status between the results performed with surgical specimens and matched endoscopic specimens. HER2 status assessed on endoscopic biopsy specimens could be reliable for treatment decisions using anti-HER2 agents in patients with advanced gastric carcinoma. Keywords: Concordance, HER2 status, endoscopic specimens, gastrectomy specimens, gastric adenocarcinoma.